Evaluation of stress distribution in an endodontically treated tooth restored with two different post and core systems in a maxillary central incisor: A finite element analysis study - Pavan, D S S Vishnu; Sampathi, Naga Lakshmi Reddy; Reddy, Upendra Natha; Neshaneni, Sathish Kumar; Medum, Shabharish Shyam Kumar; Meenakshi, Ch Meher (International Journal of Dental Materials, 2024)
Background: An endodontic post plays a crucial role in stabilizing and supporting a core restoration when insufficient coronal dentin remains after root canal treatment. It is inserted into the prepared root canal, strengthening the restoration and enabling it to endure chewing forces, thereby helping to preserve the tooth structure and overall durability of the restoration. Aim: To evaluate the biomechanical behaviour and long-term safety of high-performance polymer PEEK as an intra-radicular dental post-core material through comparative finite element analysis (FEA) with other traditional (Nickel-Chromium) post-core material. Materials and methods: CBCT scanning of a maxillary central incisor and its supporting structures was used to construct a two-3D solid model of endodontically treated teeth for finite element analysis (FEA). PEEK has a lower elastic modulus than root dentin and showed comparably more favourable stress distribution and high failure resistance than conventional post-core material. Two materials, Nickel-Chromium and PEEK, with the same crown design, were simulated to compare traditionally used post-core materials and evaluate their post-core properties. A 3D model of the maxillary central incisor area, including restorative components, was created. The masticatory load of 100 N was simulated at a 5 mm distance from the incisal edge and applied at a 45? angle to the long axis of the tooth. Results: PEEK and metal post models demonstrated similar patterns and values of maximum equivalent stresses in the overall components of the model, except for the post and crown. In the apex region of the PEEK post-core case, the values of stresses were lower than those of metal posts. Conclusion: PEEK post-core, with a lower elastic modulus than dentine, exhibited a favourable stress distribution profile at the intraradicular surface, indicating a lower possibility of root fracture than conventional post-core materials.